(untitled) (Вісник: Міжнародні відносини, 2022)
Notwithstanding the fundamental position of theoretical concepts related to law-making of international organizations, discussions about their effective juridical content still could exist. This may accordingly influence practices of international law, including questions of international economic law on implementation and regulation of cross-border investment exchange. Thus, issues of international investment law specific, including international law-making and the correspondent impact of decisions and practices of international investment arbitration, have been considered based on the letter well-known classic works on the theory of international law as well as analysis of sources and basic norms of international investment law. Scientific and practical conclusions are done about the legal sources that should be taken into account as the key ones during the implementation of international investment exchange.